2015
DOI: 10.18632/oncotarget.6223
|View full text |Cite
|
Sign up to set email alerts
|

MEF2 transcription factors: developmental regulators and emerging cancer genes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 152 publications
2
118
0
Order By: Relevance
“…The MEF2 transcription factors serve roles in muscular, cardiac, skeletal, vascular, neural, blood and immune cell development through their effects on cell differentiation, proliferation, apoptosis, migration, morphology and metabolism (30). Altered MEF2 activity serves a role in human diseases and it has recently been implicated in the initiation and progression of various types of cancer in humans (31).…”
Section: Discussionmentioning
confidence: 99%
“…The MEF2 transcription factors serve roles in muscular, cardiac, skeletal, vascular, neural, blood and immune cell development through their effects on cell differentiation, proliferation, apoptosis, migration, morphology and metabolism (30). Altered MEF2 activity serves a role in human diseases and it has recently been implicated in the initiation and progression of various types of cancer in humans (31).…”
Section: Discussionmentioning
confidence: 99%
“…Only locus showed borderline significance in our meta‐analysis dataset ( P =.011), with concordant risk effects in both studies and each individual cohort; it includes the PRRX1 gene, a putative MEF2 target involved in the development of diverse muscle types . MEF2 family, important regulators of muscular, neural, and immune system development . Of note, among other defects, subjects with MEF2C report abnormalities of GI motility, including gastroesophageal reflux disease, dysphagia, and constipation …”
Section: Discussionmentioning
confidence: 99%
“…MEF2 family, important regulators of muscular, neural, and immune system development . Of note, among other defects, subjects with MEF2C report abnormalities of GI motility, including gastroesophageal reflux disease, dysphagia, and constipation …”
Section: Discussionmentioning
confidence: 99%
“…Altered MEF2 activity has been revealed as driver of cancer development, including both hematological cancers and solid tumor. Recent study found that MEF2 genes might act as oncogenes in NSCLC [12]. …”
Section: Introductionmentioning
confidence: 99%